Beloved - Toni Morrison (UK Picador, 1988)
Sethe, an escaped slave living in post-Civil War Ohio with her daughter and mother-in-law, is persistently haunted by the ghost of her dead baby girl
Keywords: Literature (3GdCOHs; General -- Fiction; African American women; A Novel; Women slaves -- Fiction; Infanticide -- Fiction